Evaluation of Find Your Fuel: A Point-of-Service Labelling Campaign in a Military Dining Facility - Carins, Julia (Int J Environ Res Public Health, 2021)
Nutrition plays a critical role in health and job performance in physically demanding roles. Studies have shown Australian military personnel do not consume diets suited to their roles. A range of foods are provided in military dining facilities; however, personnel still need to make appropriate choices for healthier eating and to optimise performance. This study explored the effect of a labelling scheme based on military-specific nutrition guidance, over a one-month period. Food choices were evaluated in a pre-post design using plate photography (pre n = 190; post n = 159 plates); with satisfaction and behavioural influences assessed through a survey (pre n = 79; post n = 67). The results indicate the scheme had a small effect on food choice—potato and hot vegetable choices increased post-campaign for the dinner meal. On average, choices were heathier at lunch post-campaign, and less healthy at dinner. Satisfaction with the meal experience was higher after the campaign, and no difference was observed in behavioural influences (e.g., self-efficacy and other perceptions). These results are in alignment with other point-of-service labelling studies showing the limited capacity labelling schemes have on guiding consumer choices. Rather than using point-of-service labelling in isolation, additional individual and/or environmental strategies may be needed to more effectively encourage nutritious food choices by personnel.